Соціокультурні зміни повсякдення сільської людності Наддніпрянщини - Бондаренко, Г. (Народна творчість та етнологія, 2024)
У статті аналізуються зміни, що відбулися в повсякденному житті та культурі українського села Кищенці Черкаської області у ХХІ ст. Джерельною базою розвідки стали польові матеріали, зібрані авторкою в червні – серпні 2023 року методом включеного спостереження. Розглядаються особливості приватного господарювання, зміни в системі життєзабезпечення, фіксуються міграційні процеси, що відбулися та відбуваються через війну. Досліджуються глобалізаційні, інформаційні впливи на систему комунікації мешканців громади, їх соціокультурні запити та вподобання. The changes that have occurred in the everyday life and culture of the Ukrainian village of Kyshchentsi of Cherkasy region in the 21st century are analyzed in the article. The source base of the research includes field materials collected by the authoress in June-August 2023 using the method of participant observation. The peculiarities of private economic activity and changes in the life support system are considered and the migration processes that have taken place and are taking place in connection with the war are recorded. Globalization and information influence the communication system of community residents, and their socio-cultural needs and preferences are studied.